Accelerometer can accurately measure training load in badminton - Lin, Y.-C.; Liu, T.-H.; Shiang, T.-Y. (6th World Congress of Racket Sport Science, 2018)
Badminton is a racket sport, with action characterized by short duration and high intensity which combined 60-70% aerobic system and 30% anaerobic system. The ratio between action time and rest time was approximated 1:2. The purpose of this study was using accelerometer to quantify training load and physical intensity. Seven male collegiate badminton athletes (age: 21.9 ±1.7 years) with training experience (4.7 ±1.6 years) were selected as participants. They wore accelerometer on non-dominant wrist for ten minutes footwork training, rapid-shots training (four-corners and smash-net), defense and playing simulation games (single and double). Data were collected and analysed based on the top ten average acceleration every minute. The results showed that the intensity changes and physical activities could be measured in different training programs. The single simulation games showed higher intensity compared to doubles simulation games. The accelerometer can identify the physical intensity and objectively assess the physiological conditions which can provide feasible information for coaches to arrange training programs and improve the performance of the athletes.